Pengaruh Debt To Asset Ratio, Working Capital Turnover dan Sales Growth Terhadap Return On Asset: Studi pada PT Primarindo Asia Infrastructure Tbk - Iksan, Muhammad; Alwi, Alwi; Muniarty, Puji (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2023)
This research was conducted on manufacturing companies listed on the Indonesian Stock Exchange. With the aim of the research is to determine the effect of Debt to Asset Ratio, Working Capital Turnover, and Sales Growth on Return on Assets at PT. Primindo Asia Infrastructure Tbk. This research is associative research. The population in this study are companies that have gone public and have been listed on the Indonesian stock exchange for 17 years at PT. Primarindo Asia Infrastructure Tbk from 2005 to 2021. The sample in this study is 8 years. The sampling technique used is purposive sampling. This study uses secondary data using data analysis methods Classical assumption test (consisting of normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test), multiple linear regression analysis, coefficient of determination test, partial test (t-test), simultaneous test (f -test). The results of this study indicate that the Debt to Asset Ratio, Working Capital Turnover, and Sales Growth have a significant effect on Return on Assets. Furthermore, DAR has a significant effect on Return on Assets, while WCT and Sales Growth have no significant effect on Return On Assets.